Pharmacist Use of a Population Management Dashboard for Safe Anticoagulant Prescribing: Evaluation of a Nationwide Implementation Effort - Geoffrey D. Barnes; Charity Chen; Rob Holleman; Joshua Errickson; F. Jacob Seagull; Michael P. Dorsch; Arthur L. Allen; Patrick Spoutz; Jeremy B. Sussman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Direct oral anticoagulants (DOACs) have complex dosing regimens and are often incorrectly prescribed. We evaluated a nationwide DOAC population management dashboard rollout whose purpose includes pharmacist review and correction of off‐label dosing prescriptions. Methods and Results Using data from Veterans Health Affairs, we identified all patients prescribed DOACs for atrial fibrillation or venous thromboembolism between August 2015 and December 2019. Sites were grouped on the basis of the timing of moderate‐high usage of the DOAC population management tool dashboard. Effectiveness was defined as the monthly rate of off‐label DOAC prescribing and the rate of clinical adverse events (bleeding, composite of stroke or venous thromboembolism). Implementation was evaluated as the percentage of off‐label DOAC prescriptions changed within 7 days. Among the 128 652 patients receiving DOAC therapy at 123 centers, between 6.9% and 8.6% had off‐label DOAC prescriptions. Adoption of the DOAC population management tool dashboard before July 2018 was associated with a decline in off‐label dosing prescriptions (8.7%–7.6%). Only 1 group demonstrated a significant reduction in monthly rates of bleeding following implementation. All sites experienced a reduction in the composite of venous thromboembolism or stroke following dashboard adoption. There was no difference in the implementation outcome of DOAC prescription change within 7 days in any of the adoption groups. Conclusions Early adoption of the DOAC population management tool dashboard was associated with decreased rates of off‐label DOAC dosing prescription and reduced bleeding. Following adoption of the DOAC population management tool dashboard, all sites experienced reductions in venous thromboembolism and stroke events.